2002
DOI: 10.1046/j.1365-3040.2002.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

The identification of a pollen‐specific LEA‐like protein in Lilium longiflorum

Abstract: A novel pollen-specific LEA-like protein, LP28, was detected in Lilium longiflorum using two-dimensional polyacrylamide gel electrophoresis (2D-PAGE). Immunoblot analysis using antiserum raised against LP28 revealed that the protein was not found in somatic tissues or uninucleate microspores, but accumulated gradually in developing pollen following microspore mitosis. Furthermore, LP28 was abundant in germinated pollen after hydration. The cDNA clone corresponding to LP28 encoded a putative protein of 238 amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…When the callosic cell wall was digested to free the microspores, LP28 labeling was no longer detected during microspore development. This result agrees with an immunoblot analysis described previously (Mogami et al 2002). It has also been suggested that callose is present in the generative cell wall (Heslop-Harrison 1968;Tanaka 1988).…”
Section: Co-localization Of Lp28 and Callose During Male Gametogenesissupporting
confidence: 92%
See 3 more Smart Citations
“…When the callosic cell wall was digested to free the microspores, LP28 labeling was no longer detected during microspore development. This result agrees with an immunoblot analysis described previously (Mogami et al 2002). It has also been suggested that callose is present in the generative cell wall (Heslop-Harrison 1968;Tanaka 1988).…”
Section: Co-localization Of Lp28 and Callose During Male Gametogenesissupporting
confidence: 92%
“…Recently, using 2D-PAGE, we detected a novel LEA (late embryogenesis abundant)-like protein, LP28 (lily pollen protein 28), which is abundant in mature pollen (Mogami et al 2002). Here, we report the localization of LP28 during male gametogenesis by immuno-electron microscopy.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Before use in the experiments the rabbit anti serum was purified by antigen-affinity chromatography using the antigen conjugated to HiTrap NHS-activated HP (Amersham Biosciences AB, Uppsala, Sweden). OM, CM, TA and CP represent outer membrane, cytoplasmic membrane, thylakoid area and centroplasm, respectively.The immuno-electronmicroscopy was performed according to previously described method (Mogami et al 2002) using S. elongatus cells harvested at late log phase. amino acid sequence.…”
mentioning
confidence: 99%